The influence of genetic polymorphisms on performance and cardiac and hemodynamic parameters among Brazilian soccer players - Dionisio, T. J.; Thiengo, C. R.; Brozoski, D. T.; Dionisio, E. J.; Talamoni, G. A.; Braga Silva, R.; Pompermaier Garlet, G.; Santos, C. F.; Amaral, S. L. (Applied Physiology, Nutrition, and Metabolism, 2017)
This study investigated whether ACTN3 R577X, AMPD1 C34T, I/D ACE, and M235T AGT polymorphisms can affect performance tests such as jumping, sprinting, and endurance in 220 young male athletes from professional minor league soccer team from São Paulo Futebol Clube, Brazil. I/D ACE and M235T AGT polymorphisms were also analyzed according to cardiac and hemodynamic parameters. Athletes were grouped or not by age. DNA from saliva and Taqman assays were used for genotyping 220 athletes and the results were associated with performance tests. Ventricle mass, ventricle end-diastolic diameter, end-diastolic volume, and ejection fraction were assessed by echocardiogram. Arterial pressure, heart rate, and oximetry were assessed by a cardioscope. The main results of this study were that athletes who carried RR/RX (ACTN3) and DD (ACE) genotypes presented better performance during jump and sprint tests. On the other hand, athletes with ID/II genotype presented better results during endurance test, while AGT genotypes did not seem to favor the athletes during the evaluated physical tests. CC genotype (AMPD1) only favored the athletes during 10-m sprint test. Although there are environmental interactions influencing performance, the present results suggest that RR/RX ACTN3 and ACE DD genotypes may benefit athletes in activities that require strength and speed, while II ACE genotype may benefit athletes in endurance activities. This information could help coaches to plan the training session to improve the athletes` performance.